Comparison of the efficacy of ROI-C cage with Zero-P device in anterior cervical discectomy and fusion of cervical degenerative disc disease: a two-year follow-up study - Wu, Penghuan; Yang, Sifan; Wang, Yu; Wu, Qiang; Zhang, Yingze (Frontiers in Surgery, 2024)
Background: This study aimed to compare the clinical outcomes of Zero-P and ROI-C devices applied to anterior cervical discectomy and fusion (ACDF) surgery of cervical degenerative disc disease (CDDD).From January 2020 and December 2020, 56 patients with CDDD who underwent ACDF using Zero-P or ROI-C were included in this retrospective study.The outcomes included visual analogue scale (VAS) score, Japanese Orthopedic Association (JOA) score, neck disability index (NDI) score, Cobb angle, dysphagia, and bone fusion rate. Dysphagia was assessed using the Bazaz grading system. The comparison of outcomes between the two groups was based on the 2-year follow-up time point, which was defined as the last follow-up visit.The Zero-P group included 16 males and 14 females, with a mean age of 56.2 (range, 35-65) years. The ROI-C group included 11 males and 15 females, with a mean age of 57.4 (range, 36-67) years. There was no significant difference in gender and mean age between the two groups. There were no significant differences in VAS score, JOA score, NDI score, Cobb angle, dysphagia, and bone fusion rate between two groups at the last follow up visit. In the Zero-P group, the duration of surgeries involving C3-4 or C6-7 segments was significantly longer than those including C4-5 or C5-6 segments (135.0±19.0 vs. 105.6±17.5 min, P<0.05). In surgeries involving C3-4 or C6-7 segments, the operation time of ROI-C was significantly shorter than that of Zero-P (106.5±19.5 vs.112.2±20.5 min, P<0.05). There were no significant differences in the dysphagia or cage subsidence rates between the Zero-P and ROI-C groups (P>0.05). The Cobb angle in the last follow-up visit in the Zero-P group (24.4±4.5°) was significantly higher than that in the ROI-C group (18.1±2.3°) (P<0.05).Conclusions: ACDF using ROI-C device showed an efficacy similar to the Zero-P device, as well as a shorter operation time for surgeries involving C3-4 or C6-7 segments. However, ROI-C could cause more loss of Cobb angle over time, which could lead to uncomfortable symptoms.